Marketing Mix Factors Affecting Consumers’ Decision to Purchase Electric Vehicles in Chonburi Province - โทพิลา ปุณิกา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The research study on marketing mix factors affecting consumers’ decision to purchase electric vehicles in Chonburi Province has the following objectives: (1) to study marketing mix factors affecting the decision to buy electric cars of consumers in Chonburi Province, and (2) to study the expectation in deciding to buy electric cars of consumers in Chonburi Province. The sample group used in this research was 400 consumers in Chonburi Province who decided to buy electric cars. The questionnaire was used as a tool for data collection. The obtained data was then analyzed by finding percentages (Percent), mean (Mean) and standard deviations (Standard Deviation). Hypothesis testing was done using T-test and F-test (ANOVA) and Multiple Linear Regression Analysis statistics at a statistical significance level of 0.05, sorted from most to least, and the results were discussed. The results of the personal data study found that overall, the majority of the respondents were female, 224 people, aged 25-35 years, 187 people, had a bachelor’s degree, 189 people, and 173 were company employees, with a monthly income of 20,001-30,000 baht, 128 people. The results of the study on expectations of consumers in Chonburi Province in terms of purchasing decisions for electric vehicles found that most respondents gave their opinions at a high level, with an average of 4.35, consisting of reliability, followed by usability, and access to services, respectively. The analysis of data on consumer decision-making in purchasing electric vehicles in Chonburi Province found that most respondents gave their opinions at a high level, with an average of 4.32, consisting of marketing promotion, followed by price, physical characteristics and presentation, personnel, product, process, and distribution channels, respectively. The decision to buy an electric car of consumers in Chonburi Province found that most respondents gave opinions at a high level, with an average of 4.43. When considering each item, it was found that they decided to buy an electric car because of convenience and technology, followed by confidence in the brand of electric cars that they are durable and have high performance, and decided to buy because of the capacity of the electric car battery that can help them run longer, respectively.